Arquitetônica enunciativa e posicionamento estilístico do professor autor no material didático impresso da educação a distância: uma perspectiva dialógica - Vasconcelos, Gregório Pereira de (2015)
The Distance Education (DE) is a teaching modality that offers a study opportunity for people who, for many reasons, can not leave their city or state to attend a face-to-face course. The particularities of DE require, among other aspects, the use of an interactive language, which attend to the communicative needs of subjects, once they are separated by time and space. In this context, the present work investigates the enunciative architectural and the stylistic positioning of the author professor in the printed didactic material of Distance Education, in the light of the dialogic theory of Bakhtin and the Circle. We start from the hypothesis that the docent enunciations are organized in the function of the perception of his discourse by his auditory, considering that the dialogic character of language configures the stylistic positioning in the responsive act, in the interaction with other discourses and subjects. On this basis, we answer to the following research question: how does the author professor architects his enunciations in the printed didactic material of Distance Education, in order to reduce the transactional distance between the subjects inserted in this educational sphere? The epistemological framework is based on the dialogic assumptions of Bakhtin ([1919] 1993, [1926] 1976, [1940] 2013, [1979] 2010), Bakhtin/Volochínov ([1929] 2010) and Volochínov (1976), among others, whose ideas are based on the theoretical formulations of the bakhtinian enunciative theory. The investigation also takes as a basis the ideas of authors about Distance Education, as Belloni (2009) and Moore ([1993] 2002), highlighting the importance of verbal interaction to reduce the transactional distance between the subjects inserted in this teaching modality. In the present study, the inductive method was applied, and a bibliographical research was realized about the printed didactic material of the discipline Português Instrumental of the Curso de Graduação em Ciências Naturais (Licenciatura a Distância) from UFPB Virtual, aiming to collect the data that compose the corpus analyzed in this work. This is an explicative research, in which it registers and analyses the studied phenomena, with the objective of identifying its characteristics through the qualitative interpretation, and it has an applied nature, which aims new knowledges with practical application. The results evince that the docent enunciative architectonic is constructed in the movement of social orientation of the enunciation, under the valorative evaluation of the author professor speech by his auditory. The analyses also reveal that the stylistic positioning in the responsive act is drawn up in the process of verbal interaction between the author professor and the students. Thus, we ratify that the dialogic nature of language constitutes the enunciative architectonic and the stylistic positioning of the author professor, in the relation with the alterity.